Public economics and the household - Apps, Patricia; Rees, Ray, 1943- (Cambridge : Cambridge University Press, 2009)
Economic models in much of the public economics literature have been slow to reflect the significant changes towards double-income households throughout the developed world. This graduate-level text develops a more sophisticated approach to household economics, one that allows for multiple-income earners and shared decision-making. This approach is used to present a fundamentally new view of consumption. It then applies this to an analysis of tax systems, combining theoretical analysis of optimal taxation and tax reform with careful empirical study of the characteristics of income tax systems in four different countries: Australia, Germany, the UK and the USA. The book is particularly concerned with analysing, both theoretically and empirically, the impact of taxation on female labour supply, and identifying its effects on work incentives and fairness of income distribution. All this adds up to a fascinating new approach to the economics of household for researchers in both public and private sectors.
Title from publisher's bibliographic system (viewed on 05 Oct 2015).
Keywords: Women -- Employment; Tax incidence; Income distribution; Households -- Economic aspects